Energy and nutrient digestibility from mulberry (Morus alba) leaf meal for Nile tilapia - Patrícia da Silva Dias; Hanna Karolyna dos Santos; Rafael Ernesto Balen; Izabel Volkweis Zadinelo; Fábio Meurer (Acta Scientiarum. Animal Sciences, 2022)
The aim of this study was to determine the apparent digestibility coefficients and digestible values of crude protein, ethereal extract, gross energy and dry matter of mulberry leaf meal (MLM) (Morus alba L.) as Nile tilapia (Oreochromis niloticus) feed. A total of 135 Nile tilapia juveniles were used, and the indirect methodology (Cr2O3) was applied for digestibility determinations. Mulberry leave meal presented good apparent digestible coefficients of protein, ethereal extract and energy with respective values of 0.94, 0.58 and 0.39. The mulberry leave meal thus comprises adequate digestible protein and digestible energy values, similar or better than other leafy foods, presenting potential for inclusion in Nile tilapia diets.